Prediction of Mymensingh Town Future Expansion Using Space Syntax - Alam, Silvia (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Urban space changes according to different space use with the passage of time, as seen in land use, location, and land value distribution. The paper intends to analyze the change of integration core related to the growth of commercial land use through different time periods. Two phases of Commercial land-use pattern is studied. The phases are i) 1974, ii) 2013. The entire spatial structure of the commercial land use of Mymensingh reacts to the entire city system, particularly the road network pattern. In this context, this study aims to identify the influence spatial configuration exerts on the location of different types of commercial activity in terms of land use. The results of this study will help to interpret and predict the future commercial land use related to its road network. In this paper the process was conducted in the following steps: Step-01: A field survey was conducted to collect data regarding locations of commercial activity,Step-02: Land-use maps of two phases were collected to analyze the relation between commercial activity and road network,Step-03: Space syntax theory was applied to simulate the data to analyze the relationship and Step-04: Proposition.